Acute respiratory failure induced by belly dancer’s syndrome: A glance to a rare case report - Ruth Elizabeth Abraham; Gan Lay Min; Ahmad Luqman Bin Md Pauzi; Noor Hafizah Abdul Salim; Iskasymar Ismail (Turkish Journal of Emergency Medicine)
Respiratory myoclonus, also known as belly dancer’s dyskinesia (BDD), is a rare manifestation of movement disorder characterized by repetitive choreiform involuntary movements involving the anterior abdominal muscles, the diaphragm, and other respiratory muscles. Currently, there is no definite pathophysiology that clearly explains this condition. A 25-year-old male with a known case of BDD presented with an exacerbation of involuntary and continuous writhing movements of the abdominal wall muscles associated with abdominal pain and shortness of breath over the past 2 days. Subsequently, he was intubated due to worsening respiratory distress a few days after his admission. He was then put on ultrasound-guided botulinum toxin A injections of 25 units over the left hemidiaphragm regularly. His symptoms markedly improved since then as the attacks had reduced to 5–6 monthly intervals. Administration of ultrasound-guided botulinum toxin A injections may help to control the exacerbation of BDD and might be an option for cases refractory to medical treatment and phrenic nerve ablation.